2018
DOI: 10.1016/j.rbms.2018.10.020
|View full text |Cite
|
Sign up to set email alerts
|

Migrant extractability: Centring the voices of egg providers in cross-border reproduction

Abstract: This paper explores reproductive justice from the perspective of those at the beginning of the value chain of reproduction. This vantage point of egg providers can help lend important insights into the wider processes of family-making across borders today. It centres on ethnographic research conducted on contemporary cross-border egg provision performed by female migrant workers in Spain. Through this intersectional perspective, we stand to gain deeper insights into cross-border reproduction more widely. Egg p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…Michal Nahman's article, 'Migrant extractability: Centring the voices of egg providers in cross-border reproduction', (Nahman, 2018, this issue) focuses on egg donors or providers, who she conceptualizes as being at the beginning of a value chain of reproduction. Spain performs about 50% of egg donations in Europe, out of which 25% are carried out by migrant women, and Nahman's paper is based on ethnographic interviews with migrant egg providers in Spain.…”
Section: Circulationsmentioning
confidence: 99%
“…Michal Nahman's article, 'Migrant extractability: Centring the voices of egg providers in cross-border reproduction', (Nahman, 2018, this issue) focuses on egg donors or providers, who she conceptualizes as being at the beginning of a value chain of reproduction. Spain performs about 50% of egg donations in Europe, out of which 25% are carried out by migrant women, and Nahman's paper is based on ethnographic interviews with migrant egg providers in Spain.…”
Section: Circulationsmentioning
confidence: 99%
“…Global chains have been found to account for a multi-sited and often transnational nature of surrogacy and egg donation. 21 , 49 , 50 In her research on surrogacy in the western Russian metropolis of St Petersburg, Christina Weis 7 , 51 observed that the moral framework of worker-mothers referred to by the interviewed surrogate mothers dated back to the reproductive politics within the Soviet Union, which exceeded national jurisdictions.…”
Section: Key Concepts and Literaturementioning
confidence: 99%
“…Empirical research on the practice of gamete donation and matching shows a diverging trend: on the one hand, recipients and professionals display desire and intention to match by physical resemblance, including a shared 'ethno-racial(ized) background' (Homanen 2018;Becker et al 2005;Bergmann 2011;Cromer 2019;Krolokke 2014;Moll 2019;Speier 2016) yet, on the other hand, a more recent trend shows a desire to lighten/'whiten' offspring conceived through donor gametes (Marway 2018;Moll 2019;Nahman 2018). In 'Fertility Holidays', Speier (2016) refers to the fertility travellers' intrinsic hope for white babies as the 'reproduction of whiteness'.…”
Section: Racialised Logics and Imaginaries In Gamete Provisionmentioning
confidence: 99%
“…In Spain, Europe's most prolific egg donation country, 'white' oocytes are highly in demand by fertility travellers (Krolokke 2014). In order to provide the desired gametes, Spanish clinics are recruiting Eastern European donors (Bergmann 2011;Nahman 2018) and are enforcing a more thorough 'background check' on potential white donors from countries known for racial hybridity, such as Brazil, by asking them to outline up to three generations of 'whiteness' in order to qualify (Krolokke 2014, 59). Krolokke (2014) and Speier (2016) further show how gamete recipients are not shy of 'reiterating [their] racialized desire for whiteness' (Krolokke 2014, 63).…”
Section: Racialised Logics and Imaginaries In Gamete Provisionmentioning
confidence: 99%